Accountability of Financial Management in Gue Gajah Village - Satianihda Umri; Jalaluddin; Gamal Batara; Hendra Halim (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of conducting this research is to find out the management of APBDes in Gampong Gue Gajah in 2021 and 2022 as a comparison in fulfilling the accountability principle in accordance with Permendagri Number 20 of 2018, Permendes Number 21 of 2020, dan Permenkeu 201/PMK.07/2022. This research uses a qualitative approach with data collection methods in the form of interview documentation and observation. The results of the study are that the Government of Gampong Gue Gajah in the stages of implementation, administration, reporting and accountability has fulfilled the principle of accountability. However, at the planning, implementation, and accountability stages there is one indicator that is not in accordance with applicable regulatory standards, namely the Gampong Government has not submitted complete information regarding the implementation of the APBG in the information media, such as information regarding activity budget executors and activity implementing teams, as well as complaints addresses and the activity implementing team was late in submitting the activity report. In addition, in the administration stage there is a rationalization of mistakes made by village officials in data entry.